2021
DOI: 10.1002/biot.202100441
|View full text |Cite
|
Sign up to set email alerts
|

Rational hinge engineering of carboxylic acid reductase from Mycobacterium smegmatis enhances its catalytic efficiency in biocatalysis

Abstract: Background: Carboxylic acid reductases (CARs) represent useful tools for the production of aldehydes from ubiquitous organic carboxylic acids. However, the low catalytic efficiency of these enzymes hampers their application.Methods: Herein, a CAR originating from Mycobacterium smegmatis was redesigned through rational hinge engineering to enhance the catalytic efficiency.Results: Based on the unique domain architecture of CARs and their superfamily, a mutagenesis library of the hinge region was designed. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
4
2
Order By: Relevance
“…S6C). 67,68 However, we did not see a correlation of our experimental results to the obtained d1 values with our docked AMP-acyl TPA. Interestingly, we observed binding of MHET in the predicted srCAR structure, indicating that the bulky ethylene glycol sidechain could be accommodated at position A315 in the binding pocket (Fig.…”
Section: Sequence and Structural Insights Of Natural Cars Through Hom...contrasting
confidence: 76%
See 1 more Smart Citation
“…S6C). 67,68 However, we did not see a correlation of our experimental results to the obtained d1 values with our docked AMP-acyl TPA. Interestingly, we observed binding of MHET in the predicted srCAR structure, indicating that the bulky ethylene glycol sidechain could be accommodated at position A315 in the binding pocket (Fig.…”
Section: Sequence and Structural Insights Of Natural Cars Through Hom...contrasting
confidence: 76%
“…S6C). 67,68 However, we did not see a correlation of our experimental results to the obtained d1 values with our (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Sequence and Structural Insights Of Natural Cars Through Hom...contrasting
confidence: 55%
“…Indeed, a double mutant of a M. smegmatis CAR with 8-fold increased k cat was identified, at unchanged K m for vanillic acid. [96] Extensive protein engineering was employed to engineer the MmCAR towards selective activity on shorter chain fatty acids. A combination of directed evolution of the fulllength MmCAR and its A-domain, rational design of the terminal domains, and structure-guided semi-rational design of the Rdomain, was used to tailor substrate specificity and catalytic activity, leading to a variant that was able to generate 2.8-fold more medium chain fatty-alcohols in Saccharomyces cerevisiae.…”
Section: Chemcatchemmentioning
confidence: 99%
“…Prior studies have suggested that the ε-nitrogen atom of a conserved lysine binding pocket residue can form hydrogen bonds with the acid acyl−AMP complex, particularly with the ribose-ring oxygen atom, and that the distance (d1) between the nitrogen atom and the oxygen atom of the Lys residue and ribose ring, respectively, could be a nimble indicator of CAR activity (Figure S6C). 65,66 However, we did not see a correlation of our experimental results with the obtained d1 values with our docked AMP-acyl TPA. Interestingly, we observed binding of MHET in the predicted srCAR structure, indicating that the bulky ethylene glycol sidechain could be accommodated near position A315 in the binding pocket (Figure S7C).…”
Section: Sequence and Structural Insights Of Natural Cars Through Hom...mentioning
confidence: 99%